2005
DOI: 10.1021/ja040191w
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Tubelets

Abstract: A novel electron microscopy specimen protocol shows that the presumed phospholipid bilayer membrane ribbons that wind helically to form the cylinders known as "tubules" are actually flattened tubes. These flattened tubes are alternatively found with a helical twist about the tube's long axis or occasionally flat with no winding or twist. Flat, cylindrically wound and axially twisted segments are routinely found along a single tube's length, and at the helically wound and axially twisted segment junctions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…3 A). The EM showed a range of widths, with an average of 0.57 mm and lengths of 10-100 mm, which agrees with previously published data (23)(24)(25). These measurements were also consistent with the light microscopy images, in which the tubules were somewhat larger than the resolution.…”
Section: Dc89pc Lipid Tubulessupporting
confidence: 91%
See 2 more Smart Citations
“…3 A). The EM showed a range of widths, with an average of 0.57 mm and lengths of 10-100 mm, which agrees with previously published data (23)(24)(25). These measurements were also consistent with the light microscopy images, in which the tubules were somewhat larger than the resolution.…”
Section: Dc89pc Lipid Tubulessupporting
confidence: 91%
“…The self-assembling DC8,9PC lipid formed a mixture of smooth tubules and helical structures, as previously reported (25,30). These were easily resolved by DIC light microscopy ( Fig.…”
Section: Dc89pc Lipid Tubulessupporting
confidence: 80%
See 1 more Smart Citation
“…Matsui and Gologan [27] have observed direct structural transformations between tubules and helical ribbons, the conversion helical ribbons → tubules being 10 times faster than the reverse conversion. Mishra et al [28] have observed that the presumed phospholipid bilayer membrane ribbons that wind helically to form tubules are actually flattened tubes. iv) Lee et al [29] have proposed, for a diacetylenic amine salt, that rolling up a bilayer lamellar structure also gives rise to tubes.…”
mentioning
confidence: 99%
“…The rolling of lipid bilayer sheets into hollow cylindrical tubules has led to a number of novel nanostructured materials 13. It has been found that a number of synthetic lipids with modified head groups or acyl chains are able to self‐assemble into tubule structures in solution 4–15. The diameter of these self‐assembled tubules spans over a range from 10 nm to 1.0 μm, depending on the nature of the lipids and the conditions under which molecular self‐assembly occurs.…”
mentioning
confidence: 99%